(untitled) - O'Leary, Timothy J. (New York, 2011)
Timothy and Linda O'Leary and the Computer Information Technology Team at McGraw-Hill Higher Education offer your students a fully integrated learning program with time-tested quality and reliability. Office 2010: A Case Approach offers running case study throughout the text to help students understand the material in a consistent, relevant environment
Keywords: Microsoft Excel (Computer file),Electronic spreadsheets,Bảng tính điện tử,Phần mềm Excel (Tập tin máy tính); Computer programs,Chương trình máy tính